Rawls, la validación de la guerra justa (2008)
This article tries to reconstruct the normative approach of John Rawls about the war, from his conceptions of a non-ideal theory of justice and law of peoples -- The reconstruction includes the criteria to wage and conduct the war, and the debate about some usual attitudes to face it -- Here is remarkable that Rawls accept the tradition of just war theory and, specially, his way to insert it in a moral and historical situation of extreme limitation of war